Consensus definition of sport specialization in youth athletes using a delphi approach - Bell, D. R.; Snedden, T. R.; Biese, K. M.; Nelson, E.; Watson, A. M.; Brooks, A.; McGuine, T. A.; Brown, R. L.; Kliethermes, S. A. (Journal of Athletic Training, 2021)
Context A single, widely accepted definition of sport specialization does not currently exist. A consensus definition is necessary to guide youth sport stakeholders on topics associated with sport specialization.